Questões sociocientíficas: uma abordagem metodológica na formação inicial e continuada de professores de ciências da natureza - Carvalho, Julyana Cardoso (2019)
Reflecting on education goes beyond the discussion regarding the contents listed as specific for each school or academic level. In this respect, the ScienceTechnology-Society Education (STS) aims to scientifically literate citizens and emphasizes the need to think about attitudes and values that should be developed to citizen practice, in order to enable students to position themselves critically in the face of the phenomena that surround them. In this perspective, the studies that contemplate the STS relations in the world today in the levels of ethical reflection and in the new educational tendencies, consider the relevance of the Socioscientific Issues (SSI). These, in turn, when associated to the STS approach enable the learning of scientific, social and cultural meanings for the formation of science teachers. Considering these orientations, this work seeks to contribute to the initial and continuous formation of teachers of Natural Sciences, through the elaboration of SSI in formative moments. The methodological course included workshops aimed at initial and ongoing teacher training. Therefore, the present research has a qualitative nature and assumes the Participant Observation technique. The instruments for data collection were configured in: initial questionnaire, support material for the construction of SSI, evaluation material and field diaries. These procedures, according to the Content Analysis methodology, culminated in the elaboration of a priori categories for the analysis of the research data. As results of the Workshops, it was possible to identify little formal knowledge regarding the STS Field of Studies and its applicability to the Education area. Through the contact with this knowledge, the research subjects were able to reflect on their future and/or current practices in the classroom, in order to recognize the need to extrapolate the disciplinary contents and to work the process of teaching and learning with meaning for life. In this way, the inclusion of SSI in the context of teacher training is presented as a methodological orientation that has the potential to re-signify the disciplinary contents in order to meet the training needs of the subjects in contemporary society.